Case Report of Optic Disc Drusen with Simultaneous Peripapillary Subretinal Hemorrhage and Central Retinal Vein Occlusion - David Zhiwei Law; Francine Pei Lin Yang; Stephen Charn Beng Teoh (Case Reports in Ophthalmological Medicine, 2014)
A 52-year-old Chinese gentleman presented with right eye floaters and photopsia over one week. His visual acuities were 20/20 bilaterally. Posterior segment examination showed a right eye swollen optic disc and central retinal vein occlusion (CRVO) associated with an area of subretinal hemorrhage adjacent to the optic disc. Fundus fluorescein (FA) and indocyanine green angiographies (ICGA) of the right eye did not demonstrate choroidal neovascularization (CNV), polypoidal choroidal vasculopathy (PCV), or retinal ischemia. Ultrasound B-scan revealed optic disc drusen (ODD). In view of good vision and absence of CNV, he was managed conservatively with spontaneous resolution after two months. Commonly, ODD may directly compress and mechanically rupture subretinal vessels at the optic disc, resulting in peripapillary subretinal hemorrhage, as was likely the case in our patient. Mechanical impairment of peripapillary circulation also results in retinal ischemia and may trigger the development of choroidal neovascularization (CNV) and/or polypoidal choroidal vasculopathy (PCV), leading to subretinal haemorrhage. Compromise in central venous outflow with increased retinal central venous pressure from the direct mechanical effects of enlarging ODD results in central retinal vein occlusion (CRVO). Patients with subretinal hemorrhage and CRVO from ODD should be monitored closely for the development of potentially sight-threatening complications.